The Development of the Suez Canal and Projects Competitors - حسين, بان علي (Journal of Economics and Administrative Sciences, 2016)
The area around the Suez Canal has been chosen particularly  Sinai  to implement the new Suez Canal project parallel to the original 72-km-long channel due to the importance of the commercial site of the Arab Republic of Egypt, competing with shipping lanes, to accommodate the increasing maritime traffic  passing through the Suez canal, and to provide special services for trade world and reduce the economic cost of marine trip. The establishment of six tunnels for automobile and railway transport to Sinai The cost of the establishment of this new channel  and the establishment of the tunnels about (2.8) billion, of which 4 billion cost of the new channel. Project implementation period is one year. The new project of the Suez Canal passes in three stages, the first stage is the development of the ports of Port Said and Suez  to become as a high-quality global warehouses, regarding with ship chandlers stations , and the establishment of a number of industrial projects which surround  those areas. The second stage includes the creation of an industrial zone to host many industries such as the production of machinery and textile industry, building materials and packing factories and ship maintenance centers. The third phase is what is known as the valley of technology in Ismailia , which aims to create a technological area of high-tech industries, and complementary industries , research labs and training centers, the benefits of this project will provide a million jobs and increase national income to double the canal's revenues by about 259%. this project will be financed through the issuance of investment certificates only available to Egyptians whether individuals or institutions of different categories in Egyptian pounds. An estimate for the volume of investments in the Suez Canal, the focus of development projects by about $ 100 billion up to the year 2023 where 42 projects include the establishment of these will be on the table in front of Arab and foreign investments.